Increasing Regional Tax Revenue Through The Implementation of a Motor Vehicle Payment System - Andi Rustam; Andi Arifwangsa Adiningrat; Risfayana Hasan (Universitas Muhammadiyah Makassar, 2023)
This study aims to evaluate the increase in local tax revenue through the implementation of a motorised vehicle tax payment system. The object of research is